Faktor Penyebab Meningkatnya Angka Prevalensi Stunting di Kabupaten Timor Tengah Selatan, NTT - Babys, Salomon Andreas Mesak; Bell, Yohana; Babys, Giovany A.; Elu, Stefanus Poto (FISIP Universitas Bung Karno, 2024)
AbstractThe increase in stunting rates in the results of the tri-monthly data collection in South Central Timor (TTS) district, East Nusa Tenggara province from previously 13,441 to 13,488 in December 2024 raises fundamental questions regarding the factors causing the increase in numbers. This study is a qualitative study using stakeholder perception analysis. The paradigm used is the critical paradigm, the theory used is the theory of perception. The conclusion of this study is that the increase in stunting rates in TTS district is influenced by several factors including; parenting patterns, unwanted pregnancies; low education and awareness to follow doctor's recommendations, biological environmental factors, and unsupportive family factors. Leadership factors and convergent work that have not been maximized are the dominant factors that are seen as the cause of the difficulty in minimizing stunting rates in the districtKeywords: stunting, causal factors, TTS district, stakeholders.